Pengaruh Keaslian Merek, Pengalaman, Motivasi Terhadap Niat Berkunjung Kembali dengan Kepuasan sebagai Variabel Mediasi Pada Theme Park Dufan Impian Jaya Ancol - Metasari, Defrita; Rahmanita, Myrza; Nurbaeti, Nurbaeti; Pramanik, Purwanti Dyah; Rachmatullah, Adam (Jurnal Ilmiah Pariwisata, 2023)
The aim of this research is to analyze the influence of brand authenticity, experience and motivation on intention to revisit which is mediated by satisfaction. This research is quantitative research, with the SEM PLS method and the number of respondents was 100 respondents. The research results show that brand authenticity, experience and motivation have a significant and positive influence on satisfaction and intention to revisit. Brand authenticity, experience and motivation have a significant influence on intention to return through visitor satisfaction at the Dufan Impian Jaya Ancol Theme Park. Brand authenticity creates trust and loyalty, positive experiences create satisfaction, and strong motivation influences intent to return. The strong relationship between these three factors contributes to maintaining and increasing the popularity of the theme park, making them key elements in creating memorable experiences and encouraging repeat visits. Suggestions for Dufan Impian Jaya Ancol Theme Park Managers include maintaining brand authenticity, improving the quality of the experience, understanding visitor motivation, and creating incentive programs. Meanwhile, suggestions for Visitors include making the most of a visit by exploring the attractions and enjoying the entertainment, providing feedback for improvements, and recommending the theme park to friends and family. Keywords: Brand Authenticity, Motivation, Experience, Satisfaction, Return Intention